Faktor Risiko Terjadinya Coronavirus Disease 2019 pada Pasien dengan Komorbid Diabetes Melitus - Nikma Syalsabiela Fauzia (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Corona virus disease 2019 (COVID-19) is an infectious disease severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The clinical scope of Covid-19 varies, from asymptomatic, mild symptoms, to clinical conditions characterized by acute respiratory failure. The most common comorbidities in patients with COVID-19 were hypertension (HTN) (56.2%), followed by diabetes mellitus (DM) (30.1%), and chronic kidney disease (CKD) (17.5%). Several studies suggest that diabetes is one of the main risk factors for COVID-19. Therefore, this literature review aims to determine the risk factors for the occurrence of COVID-19 in patients with diabetes mellitus so that it can be used as a consideration for controlling risk factors and better treatment of COVID-19 patients with comorbidities. The method used in this research is literature review and literature search is carried out through the NCBI, PubMed, and Google Scholar databases. This research involves as many as 24 library sources from 2020-2021. Several studies have shown that diabetes mellitus is a major risk factor for COVID-19. This condition is associated with several macrovascular and microvascular complications that ultimately impact the patient's survival. Diabetes which is a hyperinflammatory condition that can increase susceptibility to COVID-19 with possible mechanisms of chronic inflammation, hypercoagulable state, and activation of the renin-angiotensin-aldosterone system (RAAS) and dysregulation of the sympathetic nervous system. Future research is urgently needed to provide a better understanding of the pathophysiological mechanisms underlying the association between COVID-19 and diabetes, and their clinical management